Influence of Nd:YAG or Er:YAG laser surface treatment on microtensile bond strength of indirect resin composites to resin cement. Lasers surface treatment of indirect resin composites. - Caneppele, T. M. [UNESP]; de Souza, A C Oliveira; Batista, G. R.; Borges, A. B.; Torres, C. R. (My University, 2012)
This study evaluated the influence of the surface pretreatment of indirect resin composite (Signum, Admira Lab and Sinfony) on the microtensile bond strength of a resin cement. Sixty samples made of each brand were divided into 6 groups, according to surface treatment: (1) control; (2) controlled-air abrasion with Al2O3; (3) Er:YAG Laser 200 mJ, 10 Hz, for 10s; (4) Er: YAG Laser 300 mJ, 10 Hz, for 10 s; (5) Nd:YAG 80 mJ, S15Hz for 1 min; (6) Nd:YAG 120mJ, 15 Hz for 1 min. After treatments, all the groups received an application of 37% phosphoric acid and adhesive. The pair of blocks of the same brand were cemented to each other with dual resin cement. The blocks were sectioned to obtain resin-resin sticks (1 x1 mm) and analyzed by microtensile bond testing. The bond strength values were statistically different, irrespective of the surface treatment performed, with highest values for Sinfony (43.81 MPa) and lowest values for Signum (32.33 MPA). The groups treated with the Nd:YAG laser showed the lowest bond strength values and power did not interfere in the results, both for Nd:YAG laser and Er:YAG. Controlled-air abrasion with Al203 is an efficient surface treatment method and the use of the Nd:YAG and Er:YAG lasers reduced bond strength, irrespective of the intensity of energy used.